The Efforts of Tahfidz Teachers in Improving The Quality of Memorizing The Qur’an of Santri by Using The Peer Support Education Method in Ma’had Al Muqoddasah Litahfidzil Qur’an Nglumpang Mlarak Ponorogo - Agus Budiman; Jihan Ramadhan (Educan : Jurnal Pendidikan Islam, 2019)
The activity of memorizing the qur’an in groups with peers is on teh methods carried out by tahfidz teachers in improving the quality of memorization of the santri. Where the tahfidz teacher is not just teaching, but also he must be able to guide, evaluate, and supervise the students to always memorize and improve the quality of memorization of al qur’an. One of them is by using the peer support education method in improving the quality of memorizing the qur’an of the santri. Where inside there are lots of social interactions and support. Be it from their peers, the tahfidz teacher, and the other. The purpose of this study wa fo find out how the efforts of tahfidz teachers in improving the quality of memorizing the qur’an of the santri using the peer support education method in Ma’had Al Muqoddasah Litahfidzil Qur’an, Nglumpang, Mlarak, Ponorogo. This study uses a qualitative descriptive method, and to obtain the required data, researchers use interview, observation, and documentation methods